Susceptibility of neisseria gonorrhoeae to gentamicin, chloramphenicol and other antibiotics in Manaus, Amazon, Brazil - Ferreira, William Antunes; Vasconcelos, Waldemara de Souza; Gomes, Jairo de Souza; Silva, Maria de Fátima Pinto da; Ferreira, Cristina Motta (Brazilian Journal of Sexually Transmitted Diseases, 2022)
We notify the antimicrobial tests of 83 N. gonorrhoeae isolates. The results showed that it is not viable to use penicillin and tetracycline to treat the disease. The resistance to quinolones has not precluded therapy yet. All gonococci were sensitive to ceftriaxone, and the low level of resistance to gentamicin and chloramphenicol may suggest their usage as a future therapeutic option